Donner des ailes (Recherches)
This article is based on the creative writing and visual arts workshop ‘Poems for kites’ set up, as part of the ARTLINGO project, during the academic year 2017-2018 for students enrolled in Romanian studies (language proficiency levels between B1 and C2 or heritage language speakers). We begin by presenting the aims of the workshop, how it unfolded and which students attended it, then analyse the challenges and positive outcomes of our approach, before ending with some reflections on this experimental language teaching method.